Characterization of dissolved organic matter for understanding the adsorption on nanomaterials in aquatic environment: A review. (April 2021) - Ly, Quang Viet; Maqbool, Tahir; Zhang, Zhenghua; Van Le, Quyet; An, Xiaochan; Hu, Yunxia; Cho, Jinwoo; Li, Jianxin; Hur, Jin
Abstract: Nanomaterials (NMs) have received tremendous attention as emerging adsorbents for environmental applications. The ever-increasing release into aquatic systems and the potential use in water treatment processes heighten the likelihood of the interactions of NMs with aquatic dissolved organic matter (DOM). Once DOM is adsorbed on NMs, it substantially modifies the surface properties, thus altering the fate and transport of NMs, as well as their toxic effects on (micro)organisms in natural and engineered systems. The environmental consequences of DOM-NMs interaction have been widely studied in the literature. In contrast, a comprehensive understanding of DOM-NM complexes, particularly regarding the controlling factors, is still lacking, and its significance has been largely overlooked. This gap in the knowledge mainly arises from the complex and heterogeneous structures of the DOM, which prompts the urgent need to further characterize the DOM properties to deepen the understanding associated with the adsorption processes on NMs. This review aims to provide in-depth insights into the complex DOM adsorption behavior onto NMs, whether they are metal- or carbon-based materials. First, we summarize the up-to-date analytical methods to characterize the DOM to unravel the underlying adsorption mechanisms. Second, the key DOM characteristics governing the adsorption processes are discussed. Next, the environmental factors, such as the nature of adsorbents and solution chemistry, affecting the DOM-NM interactions, are identified and discussed. Finally, future studies are recommended to fully understand the chemical traits of DOM upon its adsorption onto NMs. Graphical abstract: Image 1 Highlights: Traditional and advanced analyses for DOM adsorption are fully reviewed. Major factors to control DOM-NMs interactions are identified through literature review. DOM properties governing DOM adsorption behaviors on NMs are highlighted. Future studies are recommended of better understanding of DOM adsorption onto NMs.